Studi Pengaruh Tebal Tanah Lunak dan Geometri Timbunan terhadap Stabilitas Timbunan - Suhendra, Andryan (Bina Nusantara University, 2015)
The stability of embankment over soft soil is influenced by several factors such as subsoil and filling material properties, embankment geometry, ground water level and working load. This paper will present the analysis of influencing of soft soil thickness and embankment geometry to the stability of embankment. The analysis will be conducted using Slope/W by varying the thickness of soft soil and embankment geometry with certain embankment height and soft soil and fill material properties. The thickness of soft soil is varies in range of 2m to 15m, whereas the slope of embankment is varies in 4 condition i.e. 1:1 (vertical : horizontal), 1:1.5, 1:2, and 1:2.5, as well as the top width of embankment from 10m to 40m, with the output is factor of safety of embankment. The analysis result show the factor of safety is decreased when the top side of embankment is wider as well as when the slope of embankment is gentler. The analysis also show the influence of soft soil thickness to the embankment stability is limited to certain depth only that is in range of 7m to 10m, then the factor of safety remains constant.